PELAKSANAAN PELAYANAN REHABILITASI SOSIAL BAGI ANAK TERLANTAR OLEH DINAS SOSIAL KOTA PEKANBARU TAHUN 2021 - Muhammad Fuad Syarief; Wazni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT Social rehabilitation services are one of the duties of the Pekanbaru City Social Service in increasing protection and social rehabilitation services for neglected children. The problem in this research is the lack of follow-up and handling from the Pekanbaru City Social Service for abandoned children so that there are still many abandoned children in Pekanbaru City who have not found their families. This study aims to describe and find out the inhibiting factors for the implementation of social rehabilitation services for neglected children by the Pekanbaru City Social Service in 2021. This study uses normative theory in the form of Minister of Social Affairs Regulation Number 4 of 2020 concerning basic social rehabilitation for neglected children. This type of research is descriptive qualitative in nature to describe and explain the implementation of social rehabilitation services for neglected children by the Pekanbaru City Social Service in 2021. The subject of this research is the Pekanbaru City Social Service which is responsible for social rehabilitation and child protection. Data collection methods used in this study were interviews and documentation. Data analysis was carried out by analyzing qualitative data by summarizing, categorizing and drawing conclusions. The results of this study are the stages of implementing social rehabilitation services for abandoned children carried out by the Pekanbaru City Social Service, which is an effort by the Pekanbaru City Government as a form of responsibility and concern for PPKS, including abandoned children, starting from the initial approach, assessment, intervention planning, intervention, evaluation, referral. , and the termination is in accordance with the implementation in the field which is also supported by the rules set by the Pekanbaru City Government, it's just that there are still some obstacles in its implementation. As for the implementation of public services, there are supporting factors that are sufficient to assist the implementation of social rehabilitation services, such as the available budget, professional employees and social workers, good cooperation with other relevant agencies, such as cooperation with the Civil Service Police Unit to raid and also search for children. -abandoned children who are still on the streets of Pekanbaru City and also a conducive environment. Social rehabilitation services have weaknesses in social service facilities and infrastructure and also a lack of quality human resources for social rehabilitation administrators for neglected children. Keywords : Implementation, Public Service, Social Rehabilitation, Abandoned Children